2018
DOI: 10.1073/pnas.1721683115
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of mitochondrial DNA are not major contributors to aging of fruit flies

Abstract: SignificanceMutations of mtDNA accumulate in aging humans and other mammals to cause mitochondrial dysfunction in a subset of cells in various tissues. Furthermore, experimental induction of mtDNA mutations causes a premature aging syndrome in the mouse. To study if mitochondrial dysfunction is universally involved in shortening life span in metazoans, we generated a series of fruit fly lines with varying levels of mtDNA mutations. Unexpectedly, we report that fruit flies are remarkably tolerant to mtDNA mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 74 publications
(111 reference statements)
3
19
2
Order By: Relevance
“…To address the question if mtDNA mutations have an impact on ageing, a recent study engineered flies expressing a mutant version of the catalytic subunit of the mtDNA polymerase, thus introducing mtDNA mutations. Interestingly, in contrast with a previous study showing that even low levels of mtDNA mutations caused developmental delays in flies [60], mtDNA mutations did not broadly affect the lifespan or healthspan of adult flies [61].…”
Section: The Role Of Mitochondriacontrasting
confidence: 99%
“…To address the question if mtDNA mutations have an impact on ageing, a recent study engineered flies expressing a mutant version of the catalytic subunit of the mtDNA polymerase, thus introducing mtDNA mutations. Interestingly, in contrast with a previous study showing that even low levels of mtDNA mutations caused developmental delays in flies [60], mtDNA mutations did not broadly affect the lifespan or healthspan of adult flies [61].…”
Section: The Role Of Mitochondriacontrasting
confidence: 99%
“…Given that our mutator transgene appears to express endogenous levels of PolG transcript, we are at a loss to explain this discrepancy. Moreover, heterozygotes for the PolG knock-in allele displayed no obvious effect on lifespan [41], whereas our mutator lines displayed a dose dependent decrease in lifespan. The explanation for this difference is also unknown but may reflect differences in the mtDNA genetic background in these two studies, which we have found in unpublished work can influence lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…The experimentally obtained very high mtDNA mutation levels, which are unlikely to be found in nature, also reduce the lifespan of fruit flies. Additionally, adulthood is less sensitive to mtDNA mutations than is embryonic development …”
Section: Mitochondrial Anomalies With Agingmentioning
confidence: 99%